Penyuluhan Hukum Tentang Peraturan dan Legalitas Dalam Pembuatan Desa Wisata - Syukron Abdul Kadir (Universitas Widya Mataram, 2024)
Globalization leads to a significant increase in the economy through the tourism sector,juridically in Indonesia tourism is regulated in Law No. 10 of 2009 concerning tourism. As acountry that has abundant and diverse natural and cultural wealth. Other completeness isneeded in the tourism business that utilizes nature as one of them agriculture then requiresenvironmental documents in the form of Environmental Management efforts Life andenvironmental monitoring efforts (UKLUPL) as one of the requirements in running abusiness, one form of nature tourism is very popular today is to form a tourist village.Considering the importance of awareness for the organizers of tourist villages, theCommunity Service Team conducted counseling on the Regulations for Making TouristVillages in the Tembi tourist village. The implementation of community service received fullsupport from the management of Tembi Tourism Village. The implementation of the servicewas divided into three stages, pre-activity, implementation, followed by evaluation. Thecommunity was enthusiastic and increased their understanding of the regulations for makingtourist villages.